Analisis Unsur Hara Fosfor Lahan Sawah Pada Arca Kiri Areal Irigasi Bendung Di Kabupaten Banyumas - Agustine, Leony; Khomariah, Indah Dwi; Manurung, Rinto (CV. Utility Project Solution, 2023)
This research aim to know the soil P-total and P-available in paddy fields in the area Irrigation Dam Arca Left, Banyumas Regency, map nutrient status P in paddy fields in the area Irrigation Dam Arca Left, Banyumas Regency, and make recommendations P requirement based on P soil nutrient status. This research was conducted using the method of soil survey in March-April 2015. The determination of sample points is based on the level of accuracy in-depth review the level map with the map scale of 1: 50,000. In accordance with such precision that each then 100 hectares of paddy fields is represented by 1 sample observations. The results showed that the content of P-total in the area of high-status SLH A1f ie 41.4 mg P2O5 / 100g, while the area SLH A2F-total P content was at 40 mg status P2O5 / 100g. The distribution of P-available on the status of wetland SLH A1f very high at 17.2 ppm and at SLH status A2F high at 14.67 ppm. P fertilizer recommendations based on soil P status can be calculated by P sorption in rice plants, namely 0.20% multiplied by output per SLH in order to obtain results for SLH A1f recommendations of 118.4 kg and 113.4 kg of SLH A2F.